2020
DOI: 10.1186/s12935-020-01270-3
|View full text |Cite
|
Sign up to set email alerts
|

Fuzheng Kang-Ai decoction enhances the effect of Gefitinib-induced cell apoptosis in lung cancer through mitochondrial pathway

Abstract: Background: Our previous clinical study has shown that Chinese herbal medicine (CHM) Fuzheng Kang-Ai (FZKA) decoction is effective in treating advanced lung cancer patients through prolonging the drug resistance to Gefitinib (GFTN). Our basic study found that FZKA decoction could enhance the inhibition effect of GFTN in lung cancer by inactivating PI3K/Akt pathway. Moreover, our recent work showed that FZKA induced lung cancer cell apoptosis via STAT3/Bcl-2/Caspase-3 pathway. Thus in this study, we aim to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Our previous studies have shown that FZKA inhibited the growth of NSCLC cell lines including A549, PC9, and H1975 cells [23,25]. In the present study, we further observed the effect of FZKA on NSCLC cell growth inhibition in another NSCLC cell types including H1650 and H1299 using CCK-8 assay.…”
Section: Nsclc Cell Growth Was Inhibited By Fzka In Vitrosupporting
confidence: 74%
See 1 more Smart Citation
“…Our previous studies have shown that FZKA inhibited the growth of NSCLC cell lines including A549, PC9, and H1975 cells [23,25]. In the present study, we further observed the effect of FZKA on NSCLC cell growth inhibition in another NSCLC cell types including H1650 and H1299 using CCK-8 assay.…”
Section: Nsclc Cell Growth Was Inhibited By Fzka In Vitrosupporting
confidence: 74%
“…The injection volume was 10μL and the column temperature was maintained at 30°C. The e cacy of different batch of FZKA is dependable [23] .…”
Section: High Performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Western blot analysis was performed as described previously ( Wang et al, 2020 ). Briefly, cells (CNE-2, H1299, and HSF) were harvested, washed and lysed with 1 × RAPI buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Dziennis in 2007 showed that phosphorylated STAT3 promotes BCL-2 transcription [ 32 ]. A different study revealed that FZKA induced lung cancer cell apoptosis involving the STAT3/BCL-2/Caspase-3 pathway [ 33 ]. In our study, we showed that knockdown of ICT1 can alter the expression of apoptosis-related genes including BCL-2, BAX, cleaved caspase-3, and cleaved caspase-9 in OS cell lines.…”
Section: Discussionmentioning
confidence: 99%